The predictive value of fetal middle cerebral artery/descending aorta ratio doppler parameter in the evaluation of perinatal results of intrauterine growth restriction - Sukgen, Gokmen; Kaya, Omer (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Although there are various reasons for intrauterine growth restriction (IUGR), the main cause is inadequate utero-placental and feto-placental circulation. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To determine the predictive values of fetal middle cerebral artery/descending aorta (MCA/DA) Doppler parameter in the evaluation of perinatal outcomes in pregnancies with IUGR. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. 15 with IUGR and 35 normal newborn, who were born at the 34th gestational week or over included into the study. Doppler ultrasonography (US) measurements were performed. The ratio of pulsatility index/resistive index (PI/ RI) from MCA, umbilical artery (Umb), DA was determined. Neonatal characteristics such as Apgar scores, neonatal intensive care unit (NICU) requirement, weight and sex were also recorded. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In the IUGR group, mean MCA/DA RI-PI, MCA/UmB RI-PI were 0.88±0.19, 0.86±0.28, 1.22±0.18 and 1.55±0.39, respectively. In the control group, mean MCA/DA RI-PI, MCA/UmB RI-PI were 1.15±0.13, 1.09±0.41, 1.37±0.35 and 1.82±0.44, respectively. There were statistically significant relationship between MCA/DA PI with cord blood pH value and NICU requirement, age with gravida, parity, MCA/UmB RI, MCA/UmB PI; gravida with age and parity; parity with age, gravida, weight, MCA/DA RI, PI ratios. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Intrauterine MCA and DA Doppler US parameters of IUGR can be used safely in predicting perinatal outcomes in pregnancies with IUGR over 34 weeks.